1937
DOI: 10.1063/1.1749959
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Dye Concentration Relationships in Sensitized Photographic Emulsions

Abstract: A study has been made of the relationship between the total surface of silver halide in a photographic emulsion and the concentration of sensitizing dye necessary to produce maximum sensitizing. It was found that the amount of dye producing maximum sensitizing is directly proportional to the silver halide surface. Approximate calculations indicate that at optimum sensitizing concentration, the sensitizing dye is adsorbed to the silver halide grains in a monomolecular layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1938
1938
1964
1964

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…This desensitizing effect of sensitizing dyes when used in larger concentrations seems to be of a general nature. A very extensive and careful recent investigation by Leermakers, Carroll, and Staud (27) showed invariably the same result.…”
Section: Introductionsupporting
confidence: 53%
“…This desensitizing effect of sensitizing dyes when used in larger concentrations seems to be of a general nature. A very extensive and careful recent investigation by Leermakers, Carroll, and Staud (27) showed invariably the same result.…”
Section: Introductionsupporting
confidence: 53%
“…The results of exposure through a Wratten No. 47 filter are plotted in figure 11 on a linear scale, along with the data of Leermakers, Carroll, and Stand (9). In figure 12, values of l/2J«o for the same coatings are plotted against concentration: these show that desensitization can be measured at the lowest concentrations of dye.…”
Section: Effect Of Desensitization Ox the Optimum Dye Concentrationmentioning
confidence: 94%
“…Earlier data from these Laboratories had indicated that desensitization by practically useful dyes was associated primarily with the use of excessive concentrations. Leermakers, Carroll, and Stand (9) have given examples of the change in sensitivity to light transmitted by the standard tricolor filters, corresponding to varying concentrations of dye. Sensitivity to exposure through the red and green filters passed through well-defined maxima as the concentration was increased; sensitivity to light transmitted by the blue filter remained practically constant for all concentrations up to the value corresponding to the red and green maxima, and then decreased rapidly.…”
Section: Introductionmentioning
confidence: 99%